Determination of Heavy Metals, Arsenic, and Aluminum Content in Pumpkin Seed Herbal Substance and Native Products, by Inductively Coupled Plasma Mass Spectrometry - S. V. Ovsienko; V. M. Shchukin; E. A. Blinkova; N. E. Kuz’mina (Регуляторные исследования и экспертиза лекарственных средств)
Pumpkin seeds belong to the so-called native products. Their characteristic feature is that they can be consumed directly, without prior extraction of the starting material. All elemental toxicants contained in pumpkin seeds are transferred in full to the native product. Therefore, it is important to study specific aspects of elemental toxicant accumulation by pumpkin seeds.The aim of the study was to determine the content of heavy metals, As, and Al in pumpkin seed herbal substance and native products, and to assess the degree of accumulation of these elements, depending on the vegetation area.Materials and methods: the study evaluated pumpkin seed native products by Russian manufacturers as well as pumpkin seeds harvested in areas with different anthropogenic load. The sample preparation was performed by microwave digestion, and the determination of the elemental toxicants was perfomed by inductively coupled plasma mass spectrometry.Results: the pumpkin seeds were shown to contain essential, probably essential, potentially toxic, and toxic elements. The authors performed comparative analysis of the elemental composition of pumpkin seeds as well as seeds, grains, and beans of various oil-bearing, grain, and leguminous crops.Conclusions: the content of the specified elemental toxicants (As, Cd, Hg, Pb) in the tested samples of pumpkin seed herbal substance and herbal medicinal products did not exceed the limits established by the Russian Pharmacopoeia. The unspecified toxic elements were either absent in pumpkin seeds (Tl) or found in trace amounts (Al). The content of a number of essential elements (Zn, Fe, Mn, Cu, Mo, Cr) in pumpkin seeds was higher than in the seeds of many oil-bearing crops. The vegetation area had no significant influence on the content of the tested elements in the pumpkin seeds. Pumpkin seeds are capable of accumulating abnormally high amounts of Cd, Co, and Ni in areas with high environmental pollution.